The Role of Community in Sustainable Tourism. Case Study: Girsang Simpangan Bolon - Fakhry Perdana Koara (International Journal of Architecture and Urbanism, 2021)
Abstract. Sustainable tourism must consider three aspects of sustainability, namely economic, social and environmental aspects. To support sustainable tourism development, the community's role in tourism development or Tourism Based Community (TBC) is one of the critical principles that must be fulfilled because it is the component closest to and tied to regional tourism. This research examines the community's role in Girsang Sipangan Bolon District, Simalungun Regency in the development of sustainable tourism. The study uses quantitative methods by collecting data through distributing questionnaires. The observations show that the participation of local communities related to sustainable tourism in Girsang Sipangan Bolon is classified as good with an overall average score of 3.8 out of 4.5 for several indicators of local community participation in sustainable tourism